Elektronikkylning av radarutrustning med hjälp av avancerade kylteknologier - Schloenzig, Erik; Wassén, Erik (My University, 2016)
This thesis work is a result of studies done at Saab Surveillance, with the objective to evaluate cooling technologies and find out which of them that are or are not suited to be implemented on a generic house and plug-in units, meeting the higher thermal demands of the future. This task includes five products, all with their own pros and cons created by Thermacore, a company of advanced cooling technologies with its European head office located in Ashington, England. First up was to realize under which circumstances these products were supposed to operate. This included application areas like land, sea and air which all have different grades of requirements set for today’s generic houses and plug-in units. To find the answers for these factors a trip to England and Thermacore was made and together with their engineers, hypothetical thermal simulations could be developed but also gather a wide understanding of each technology´s possibilities and limits. When all the information was assembled an extended evaluation process could be completed. The result showed that the superior cooling technology differed depending on mainly two things. The first one was taken in regard of which application area it was supposed to operate in but also where it is being implemented either in a generic house or on a plug-in unit. In conclusion of this report it showed that for the plug-in unit the recommended technology for land and sea units was to be a heat pipe assembly. The construction contains four flattened heat pipes encapsulated in an aluminum plate. Regarding air applications and foremost the fighter jets, the most suited technology was the k-Core. It will endure the exposure of both high vibrations and shocks but above all in an effective way cool the system. For the generic houses and those operating on land and sea it would once again be a heat pipe assembly that is the optimal solution, though those working in air applications the loop heat pipe is the better fit. These results will be discussed and visualized in the report.
Keywords: Informations- och kommunikationsteknik; Materialvetenskap; Innovation och entreprenörskap (nyttiggörande); Elektroteknik och elektronik; Energiteknik; Information & Communication Technology; Materials Science; Innovation & Entrepreneurship; Electrical Engineering, Electronic Engineering, Information Engineering; Energy Engineering